CD40 expression in Wehi-164 cell line - Karimi, Mohammad Hossein (Springer Netherlands, 2010)
CD40-CD154 interaction is an important process for cellular and humoral immunity regulation and can be effective in the body’s defense against tumors. In the present study, we evaluated the expression of CD40 in Wehi-164 cell line. CD40 expressions on the cell surface and in the cytoplasm were assessed by flow cytometry and intracellular staining assay, respectively. Also, the mRNA expression was identified by real time-PCR. The obtained results showed the high mRNA and cytoplasmic protein expression of CD40 but no surface expression. These results suggest that the Wehi-164 cell line down regulates expression of CD40 on the surface for evasion of immune system.